ANALYSIS OF REPRESENTATIVE ILLOCUTIONARY ACTS IN DOCUMENTARY MOVIE ON THE MINIMALISTS : LESS IS NOW - Widha Istika Winekas Hartono; Dias Andris Susanto; Faiza Hawa (JOEL: Journal of Educational and Language Research, 2022)
This study aims to determine the types and describe the most dominant and least appearance of representative illocutionary acts in the documentary movie entitled "The minimalist less is now." This study used a qualitative descriptive method and applied the speech act theory by John R Searle (1979). The data were obtained through the listening method and note-taking technique. This study reveals that eight types of representative illocutionary acts are retelling, asserting, arguing, informing, explaining, reporting, reminding, and complaining. Its retelling appears as the most frequent type of representative illocutionary acts with a frequency of 47 data (25.13%) and its complaining is the least representative type of illocutionary acts with a frequency of 8 data (4.3%). This study can be a reference if someone wants to find out the contents of an utterance in this movie as a source of learning and an additional source in their literary work.